Evaluation of Role of Functional Endoscopic Sinus Surgery in Patients of Sinonasal Diseases & Nasal Polyposis - Bajoliya, Sunil; Maru, Y K; Goswami, Reema (International Journal of Medical Research and Review, 2015)
Introduction: Functional Endoscopic Sinus Surgery has opened up a new horizon in the management of chronic sinonasal (allergic & non allergic) diseases & nasal polyposis. Functional Endoscopic sinus surgery (FESS) is now a days a common and excellent method for the treatment of most of the diseases in the area of nose and paranasal sinuses, like chronic rhinosinusitis with and without nasal polyposis. Materials and Method: In this study we have selected 80 patients of chronic sinonasal (allergic & non allergic) diseases & nasal polyposis attending the department of otorhinolaryngology. All the patients were pre-operatively evaluated clinically, radiologically as well as endoscopically. Diagnostic nasal endoscopy revealed various pathological abnormalities in the middle meatus and anterior ethmoid region. Even after complete pre-operative evaluation, initially patients were managed medically according to their symptoms and were observed for 6 weeks. All 80 patients underwent for functional endoscopic sinus surgery, using the Messerklinger’s approach. Result: The overall result reveal that 85.49% patients considered themselves asymptomatic or improved following surgery. No major complication directly related to FESS occurred in this series. The important finding were, osteomeatal complex obstruction seen in 88.75%, polyp in nose in 46.25% of cases. Radiological evaluation done by coronal section (axial & sagital if needed) CT scanning revealed the maxillary sinus most common site of mucosal involvement 76.25%% followed by anterior ethmoid sinus in 53.75% cases. Frontal and sphenoid sinuses were involved in 26.25% and 15% cases respectively. Conclusion: FESS is highly effective in controlling symptoms of chronic sinonasal diseases with or without polyposis.